Terengganu State Decision Support System for School-leavers (TeSDeSS) - Raju, Rajeswari; Nurulhikmah Syed Yasin, Sharifah; Adilin Mohd Abdul Majid, Hayati; ‘Aisyah Sa’dan, Siti; Ismail Abd Wahab, Zawawi; Sabapathy, Elangkeeran; Subramaniam, Geetha (International Journal of Engineering and Technology, 2018)
Year after year, the numbers of school-leavers increase significantly. Some of them continue their journey by furthering their studies in higher education. The ones that can further their study usually are the ones that know their interests and have achieved good results in government examinations, and hence are qualified to apply to government universities or tertiary institutions such as matriculation, polytechnic, and others withÂ their targeted or desired academic degrees. But, this differs for school-leavers who have dismal grades in government examination (dropout students), most of whom just give up on their first application to government tertiary institutions. The Terengganu state government hence wanted to come out with a system that can help to minimize this problem. In this proposed research,it was found that school drop-outs from Terengganu are not aware of the existing opportunities to further their studies with moderate or low grades, and currently there is no platform that unites all education and skills institutes inone single platform. This proposed research will cater for all the identified problems, to make this research feasible, and the rule-based system will be used as the theoretical proponent.Â Â